Pengaruh Konflik Peran Ganda Terhadap Stres Kerja Dengan Tipe Kepribadian Neuroticism Sebagai Variabel Moderator - Syadza Noverta Vizia Zelfi Syadza; Rizal Kurniawan (LPPM Politeknik Pratama, 2023)
Hospital nurses are a workforce that has enormous responsibilities and almost no time for holidays. The difficulty for these female nurses is managing time for both roles, giving rise to role conflict within the nurses which has an effect on stress at work, especially for people who have neuroticism personalities. This research aims to gain knowledge about the effect of multiple role conflict on work stress and neuroticism personality as a moderator variable. The research sample was 200 samples with the characteristics that would be used as samples determined by the researcher. Based on the analysis in this study, it was found that the results of simple linear regression (t= 24.24, p = 0.000 (p < 0.01) and R2 were 0.748, namely 74.8% was influenced by role conflict and 25.3% was influenced by other factors and for the MRA test the results were (t= 2.07, p = 0.040 (p < 0.05) and R2 were 0.764%, namely 76.4% was influenced by neuroticism personality as a moderator and 23.6% is influenced by other factors. It can be concluded that there is an influence of dual role conflict on work stress and the neuroticism variable can moderate or strengthen the influence of dual role conflict on the job stress of female nurses at RSU Padang.